Effect of Carfentrazone associated with Diquat and Glufosinate on pre-harvest desiccation of soybean - Altmann, Henry Matheus; Moreira, Daicon Godeski; Adamski , Jonatan Leandro; Antonowiski , Mauricio; Potelicki, Victor Almir; Figura, Suzana (Revista de Ciências Agroveterinárias, 2024)
Pre-harvest desiccation of soybeans is carried out mainly with the aim of standardizing plant maturation, anticipating harvest, controlling controlled plants and reducing loss of seed quality. The objective was to evaluate the efficiency of the herbicide carfentrazone associated with diquat and glufosinate for pre-harvest desiccation of soybeans. The experiment was conducted on the Mallon agricultural farm, in the municipality of Canoinhas-SC, during the 2021/2022 harvest. A randomized block design was used, with five treatments and four replications. The treatments were constituted as follows: (I) control – without herbicide; (II) glufosinate; (III) glufosinate + carfentrazone; (IV) diquat; (V) diquat + carfentrazone. Each replication was composed of plots of 15 m². The application of the products occurred at the R7 stadium. 3. The level of defoliation was higher in the treatment composed of diquat + carfentrazone (V), however the treatment composed of diquat (IV) also obtained significant defoliation. The other treatments did not achieve defoliation levels greater than 40%. It is concluded that the herbicide diquat alone or associated with carfentrazone promotes the highest levels of defoliation.